G500(P) Early nutrition for later health: why 'early' should start in pregnancy. (27th April 2015) - More, J
Abstract : Aims: To research the evidence base underpinning the short and long term effects of nutritional status and insufficiency during fetal and infant life To assess the knowledge base of healthcare professionals and the resources available to them and parents to optimise nutritional advice for families during this key developmental period Methods: An extensive literature search and interviews with key experts in the field Qualitative and quantitative surveys of 150 healthcare professionals and 1, 000 mothers/mothers-to-be to understand perceptions/attitudes and the level of knowledge about the impact of nutrition and lifestyle during preconception, pregnancy, infancy and the preschool years on health outcomes. Results: Maternal nutritional status and BMI during preconception and pregnancy impacts on programming and development in the fetus, affecting short and long term health outcomes of mother and child Maternal obesity and excess gestational weight gain affects hormonal balance and increases risk of complications in pregnancy and obesity in the infant and childhood Maternal nutritional status and type of infant feeding affects growth, bone health, risk of some infections and atopic disease in children with a family history of allergy Knowledge base and training of some HCPs is inadequate and most would welcome more training and consultation time Weighing during pregnancy, calculating pre pregnancy BMI and advising on suitable gestational weight gain is not routine Advice on healthy eating and supplementation to ensure adequate intakes of folate, vitamin D, iodine, iron and omega 3 during preconception and pregnancy is not routine Mothers would welcome more advice and support during preconception and, pregnancy and on early life nutrition Conclusion: Families need updated, consistent evidence based information on nutrition and weight management preconception, during pregnancy and early life and HCPs need more time, resources and training to effectively deliver this.